THE RELATIONSHIP BETWEEN NATIONAL INCOME AND COMMUNITY EMPOWERMENT: A DEFENSE ECONOMICS PERSPECTIVE - Rizqiah, Khairul; Murtiana, Sri; Suwito, Suwito; Sambas, Maimunah (Jurnal Pertahanan dan Bela Negara, 2025)
Income inequality can hinder the relationship between national income and community empowerment. High inequality allows the rich to become richer while the poor struggle to escape poverty. This disparity limits access to public services, employment, and education, thereby obstructing empowerment. This study analyzes the relationship between national income and community empowerment from a defense economics perspective. It provides policy references for optimizing national income allocation to strengthen economic resilience as a non-military defense component. A quantitative correlational design was employed using Indonesia’s time series data (2013–2022), with Gross Domestic Product (GDP) as the independent variable and the Human Development Index (HDI) as the dependent variable. Results indicate a significant positive correlation (r = 0.982, p < 0.05). However, while GDP more than doubled from 9,084 trillion rupiah (2013) to 19,588 trillion rupiah (2022), HDI increased only moderately from 68.31 to 72.91, suggesting diminishing returns. The study concludes that although national income positively influences empowerment, equitable distribution and broader economic access are essential to ensure welfare improvements. From a defense economics perspective, community empowerment should be reoriented as a strategic component of national economic resilience, integral to a comprehensive non-military defense system.